2013
DOI: 10.1111/ans.12475
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of low‐dose celecoxib in reducing post‐operative paralytic ileus after major abdominal surgery

Abstract: The use of low-dose COX-2 inhibitor over a short period of time decreases the paralytic ileus rates and does not cause any significant morbidity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…The sympathetic neural response to intrusion of the peritoneal cavity and handling of bowel causes a reactive hypomotility of the GIT, which usually fades quickly upon abdominal closure, but prolonged ileus can occur, has been shown to be associated with increased IL‐6 and leucocyte infiltration of the bowel , and has a positive correlation with rates of AL . Here again evidence shows that inhibiting the inflammatory axis via COX‐2 improves ileus . Some clinical studies comparing laparoscopic with open surgery suggest a relationship between decreased inflammation, as evidenced by a lower CRP level postlaparoscopy, with lower ileus and AL rates , but caution needs to be exercised in interpreting these results as correlation does not always imply causation.…”
Section: The Role Of Inflammationmentioning
confidence: 99%
“…The sympathetic neural response to intrusion of the peritoneal cavity and handling of bowel causes a reactive hypomotility of the GIT, which usually fades quickly upon abdominal closure, but prolonged ileus can occur, has been shown to be associated with increased IL‐6 and leucocyte infiltration of the bowel , and has a positive correlation with rates of AL . Here again evidence shows that inhibiting the inflammatory axis via COX‐2 improves ileus . Some clinical studies comparing laparoscopic with open surgery suggest a relationship between decreased inflammation, as evidenced by a lower CRP level postlaparoscopy, with lower ileus and AL rates , but caution needs to be exercised in interpreting these results as correlation does not always imply causation.…”
Section: The Role Of Inflammationmentioning
confidence: 99%
“…Studies examining opioid-sparing analgesic regimens have shown a decrease in postoperative ileus. Lidocaine, 2 celecoxib, 3 magnesium, 4 and epidural analgesia 5 have all been shown to decrease opioid consumption and decrease risk of postoperative ileus formation. Postoperative ileus contributes significantly to both cost and LOS in patients undergoing colorectal surgery.…”
mentioning
confidence: 99%
“…Holte and colleagues 31 showed in a retrospective study that celecoxib was an independent predictor of anastomotic leaks in patients who had colonic surgery. On the contrary, Gorissen and colleagues 67 and Raju and colleagues 33 could not demonstrate the association. 31 33 67 In fact, the authors indicated that the risk of anastomotic leaks was higher after the use of non-selective NSAIDs than with coxibs.…”
Section: Perioperative Nsaids and Anastomostic Leaksmentioning
confidence: 86%